Microteaching Setting during the COVID-19 Pandemic from the Author’s Point of View - Simamora, Roy Martin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Microteaching is one such teacher training technique which helps the teacher trainee to master the teaching skills and develop teaching strategies. The impact of the COVID-19 pandemic has made microteaching courses conducted online. This study aims to analyze the microteaching experience of Performing Arts Education students in a microteaching course during the COVID-19 pandemic. The microteaching session is divided into two sessions: online theory-based microteaching sessions and offline practice-based microteaching session. This study used a qualitative research. The research design used is the author's point of view.The author has direct contact with the people, situations, and phenomena being investigated. Data analysis techniques are carried out by systematically observing and recording the symptoms that appear in the object of research. In this microteaching setting, the author observes how students develop their own teaching and learning processes by planning, teaching, observing, evaluating, and reflecting on learning. The findings of this study indicated that the implementation of online and offline microteaching during the COVID-19 pandemic has its own advantages and disadvantages. In addition, the technical side also needs attention. The students still have not shown maturity in mastering the principles of teaching in the classroom. This study is used as a means to improve student teaching to become future educators in unexpected situations.